Proteasome and Organs Ischemia-Reperfusion Injury: A Review - Joan Oliva (Recent Research Advances in Biology Vol. 10, 2021)
The treatment of organ failure on patients requires the transplantation of functional organs, from donors. Over time, the methodology of transplantation was improved by the development of organ preservation solutions. The storage of organs in preservation solutions is followed by the ischemia of the organ, resulting in a shortage of oxygen and nutrients, which damage the tissues. When the organ is ready for the transplantation, the reperfusion of the organ induces an increase of the oxidative stress, endoplasmic reticulum stress, and inflammation which causes tissue damage, resulting in a decrease of the transplantation success. However, the addition of proteasome inhibitor in the preservation solution alleviated the injuries due to the ischemia-reperfusion process. The proteasome is a protein structure involved in the regulation the inflammation and the clearance of damaged proteins. The goal of this review is to summarize the role of the proteasome and pharmacological compounds that regulate the proteasome in protecting the organs from the ischemia-reperfusion injury.